The Effect of Electronic Health Record (EHR) Implementation on Collaboration, Documentation and Quality of Nursing Services at Mitra Keluarga Gading Serpong: Descriptive Analysis - Fenty Efendy; Muhammad Hadi; Melati Fajarini; Fitri Arofiati; Tini Suminarti (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2025)
Background: The Hospital Management Information System (SIMRS) is an information technology that integrates all hospital service processes through a network of coordination, reporting, and administrative procedures to produce accurate and timely information. The implementation of the Electronic Health Record (EHR) is a digital innovation in healthcare that supports improved service quality, patient data integration, and the direction of national health development policies that emphasize technology-based promotive and preventive efforts. Objectives: This study aims to determine the effect of EHR implementation on collaboration, documentation, and service quality at Mitra Keluarga Gading Serpong Hospital. Methods: This study used a descriptive design with stratified random sampling with proportional strata. The sample consisted of 97 nurses with more than six months of service. Data analysis was conducted using the Partial Least Squares (PLS) method to test the research hypotheses. Results: The analysis results show that there is a significant effect of EHR implementation on collaboration with a p value of 0.000 < 0.05. EHR implementation also affects documentation with a p value of 0.000 < 0.05. In addition, there is a significant effect of EHR implementation on service quality with a p value of 0.000 < 0.05. Conclusion: These findings indicate that EHR implementation can enhance collaboration among healthcare professionals, improve the quality of nursing documentation, and enhance overall service quality. Data integration and easy access to information through the EHR have had a positive impact on the service process at Mitra Keluarga Gading Serpong Hospital. Keywords: Collaboration, Documentation, EHR, Quality of Service